Antibody approaches to prepare clinically transplantable cells from human embryonic stem cells: Identification of human embryonic stem cell surface markers by monoclonal antibodies. Issue 7 (25th February 2014) - Choi, Hong Seo; Kim, Won‐Tae; Ryu, Chun Jeih
Abstract Human embryonic stem cells (hESCs) are unique cell populations, possessing both unlimited self‐renewal capacity and pluripotency, i.e. the potential to give rise to all kinds of specialized cells in the human body. Marker molecules expressed on the surface of hESCs are important for the identification, characterization, and clinical application of hESCs. Compared with conventional genomics‐ or proteomics‐based approaches, generating monoclonal antibody (mAb) libraries against hESCs using alternative methodologies expands the repertoire of mAbs raised against non‐protein markers, for example, glycolipid antigens. Additional information about the conformation and post‐translational modification of surface molecules can also be obtained. In this article, we review how mAb libraries against hESC surface markers have been developed using whole‐cell and decoy immunization strategies.